Treatment advances in Vitiligo: An Updated Review - Binti Ismail, Ishrat; Jabeen Bhat, Yasmeen; Shurjeel ul Islam, Mohd (Dermatology Practical & Conceptual, 2025)
Introduction Vitiligo is a common disorder of depigmentation caused by the progressive destruction of melanocytes that affects the skin, hair, and mucous membranes, clinically presenting as depigmented macules and leukotrichia. This condition, affecting millions of people worldwide, has a significant psychosocial burden on patients’ quality of life, particularly in relation to skin colour. The etiopathogenesis of this disorder is obscure, but multiple factors contribute to the loss of melanocytes in the skin, like oxidative stress, inflammation, genetics, and autoimmunity. The treatment of vitiligo has been challenging over the past years, but recent developments in understanding the etiopathogenesis of the disease have paved the way for the development of more effective and promising therapeutic treatment options. Objective The aim of this review was to provide an overview of the underlying mechanisms and highlight the latest advances in the treatment of vitiligo. Methodology This review was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Metanalyses) guidelines. A comprehensive search of the literature was carried out through the PubMed electronic database from inception to 31 December 2023 using the following search terms “vitiligo” AND “JAK inhibitors”, “vitiligo” AND “prostaglandin”, “vitiligo” AND “afamelanotide”, “vitiligo” AND “antioxidants”, “vitiligo” AND “vitamin D3”, “vitiligo AND “statins”, “vitiligo” AND “TNF-alpha”, “vitiligo” AND “interleukin”, “vitiligo” AND “light therapy”. Two independent reviewers screened titles, abstracts, and full texts to select papers dealing with vitiligo and its treatment. Conclusion The advent of treatment modalities like Janus kinase inhibitors, prostaglandin analogues, antioxidants, TNF-α inhibitors, targeted phototherapy, and excimer lasers has revolutionized the therapeutic possibilities, offering a ray of hope to the individuals suffering from this devastating condition.